InTEIrviews: An ODD for Qualitative Interviews in the Humanities - Marie Puren; Florian Cafiero (Journal of the Text Encoding Initiative)
Qualitative interviews are a crucial research method for many disciplines in the humanities and social sciences. Yet apart from rare initiatives, interview transcriptions are seldom shared with other researchers. Even when they are, annotations are mostly absent, and rarely standardized or designed to be read by anyone but the initial research team. In this paper, we advocate for a more open management of these resources, and present a proposition for an XML-TEI–conformant standard that allows for their accurate transcription and annotation. The ODD we present is aimed at facilitating systematic analyses of corpora of interview transcriptions, as well as ensuring wider dissemination and reusability of these resources. Relying entirely on existing TEI elements to create this ODD, we combine primarily the elements and attributes declared by the modules “Transcription of Speech” and “Language Corpora.” This ODD is designed to help describe the actual development of the interview, transcribe the interpretations made by the researcher(s), and tackle ethical or anonymity issues.